Greenway Planning Context in Istanbul-Haliç: A Compulsory Intervention into the Historical Green Corridors of Golden Horn - Hoşgör, Zerrin; Yigiter, Reyhan (Informa UK Limited, 2011)
Abstract In the last two decades, planners and landscape architects have been concerned with the open space planning concept called ‘greenway planning’. This approach aims at nature protection that balances both conservation and growth, creating livable environments and maintaining open spaces. In Istanbul, the functional and spatial connectivity of greenways can protect the local landscape against urbanization and population growth problems. This study aimed to emphasize the natural and cultural heritage in an ecologically based planning approach. After taking into consideration the current greenway planning process in Europe and America, a planning strategy was determined for Halic reflecting all characteristics of Istanbul and possibly representing the first greenway example in the city. Halic was degraded by industrialization, urbanization, migration and inappropriate land use plans through the ages and existing greenway corridors had disappeared. As a result, current greenway planning strategies were...